Development, manufacture and assessment of Clobetasol 17-propionate cream formulations - Fauzee, Ayeshah Fateemah Beebee (Rhodes University, Faculty of Pharmacy, Pharmacy, 2011)
Eczema or dermatitis is the most common dermatological condition accounting for one-third of all diagnoses in the total population surveyed in South Africa. The prevalence of seborrhoeic dermatitis, extreme photodermatitis and severe psoriasis has increased markedly over the last decade and this increase may be ascribed to the HIV epidemic, first diagnosed in South Africa in 1982. Potent innovator corticosteroids, such as clobetasol 17-propionate (CP) that are used to treat skin disorders, are expensive and there is therefore a need for the production of generic topical corticosteroid products. Formulation and manufacturing processes can be challenging aspects for formulation scientists to produce a robust product that will elicit an appropriate and desirable pharmacokinetic-pharmacodynamic profile. Laboratory scale CP creams were manufactured using different concentrations of Gelot® 64 and propylene glycol in order to establish a composition that would produce a formulation, with similar physical and chemical characteristics and in vitro release profile as an innovator product, Dermovate®. These formulations were assessed in terms of their viscosity, spreadability, pH, content uniformity and in vitro release characteristics using a Franz diffusion cell apparatus. A formulation containing 3% w/w Gelot® 64 and 46% v/v propylene glycol (CPLS-02) was found to exhibit similar viscosity and spreadability characteristics and released CP in a manner similar to Dermovate®. The mechanism of drug release was evaluated using mathematical models such as zero order, first order and Higuchi models. In addition, the in vitro release profiles were characterised by use of difference (f1) and similarity (f2 and Sd) factors. A scale-up formulation with the same % w/w composition as the laboratory scale was also investigated following manufacture using a Wintech® cream/ointment mixer. A Central Composite Design approach was used to investigate the effect of process variables on the performance of the scale-up cream formulations. The homogenisation speed, anchor speed, homogenisation time and cooling time were the process variables investigated. Thirty scale-up batches were manufactured and analysed in terms of their viscosity, spreadability, pH, % drug content and cumulative % drug released per unit area over 72 hours. Model fitting using Design-Expert® software was undertaken and revealed that a correlation between the process variables and the cream responses was most suitably described by quadratic polynomial relationships. The homogenisation speed had the most significant effect on the quality of the scale-up formulations, whereas the anchor speed had a secondary effect on the measured responses, for the formulations investigated. The qualitative interpretation and statistical analysis of the in vitro release data from the scale-up formulations using ANOVA and the f1, f2 and Sd factors revealed that one scale-up batch (CPSU-04), for which the process variables were a homogenisation speed of 1900 rpm, an anchor speed of 35 rpm, a homogenisation time of 100 minutes and a cooling time of 100 minutes, released CP at a similar rate and extent to Dermovate®. A diffusion-controlled mechanism appeared to be predominant in these formulations. A human skin blanching study, using both visual and chromameter assessments, was performed to establish whether batch CPSU-04 was bioequivalent to Dermovate®. The bioequivalence of the selected scale-up formulation to Dermovate® was confirmed, following the calculation of a 90% CI.
Keywords: Adrenocortical hormones; Adrenocortical hormones -- Physiological effect; Adrenocortical hormones -- Testing; Drugs -- Testing; Drugs -- Development; Dermatopharmacology